Pharyngocutaneous fistula after total laryngectomy: Prevalence and risk factors - Petronella Pettersson; Rasmus Blomkvist; Krzysztof Piersiala; Elin Marsk; Alexandra Elliot; Björn Palmgren; Claes Mercke; Linda Marklund; Rusana Bark (PLoS ONE, 2026)
Objective To determine the prevalence and identify associated risk factors of pharyngocutaneous fistula following total laryngectomy. Methods Medical records of 160 patients diagnosed with laryngeal cancer between 2000–2021, subsequently undergoing total laryngectomy at Karolinska University Hospital, were analyzed for demographics, comorbidities, tumor characteristics, treatments and postoperative outcomes. Uni- and multivariate analyses were used to identify risk factors for pharyngocutaneous fistula. Results Pharyngocutaneous fistula developed in 28 patients (17.5%). Univariate analysis identified cardiovascular disease (OR 2.50; 95% CI 1.00–6.28), preoperative hemoglobin <110 g/L (OR 5.34; 95% CI 1.74–16.45), prior radiotherapy (OR 3.78; 95% CI 1.24–11.52), preoperative tracheostomy (OR 2.44; 95% CI 1.05–5.72), pharyngectomy (OR 8.47; 95% CI 2.46–29.17), neck dissection (OR 2.52; 95% CI 1.06–6.00), pectoral flap reconstruction (OR 10.83; 95% CI 1.88–62.49) and postoperative infection (OR 28.44; 95% CI 9.00–89.81) as significant risk factors. In multivariate analysis only pharyngectomy (OR 7.18; 95% CI 1.08–47.63; p = 0.041) and postoperative infection (OR 24.94; 95% CI 6.66–93.46; p < 0.001) remained independent. Conclusions Pharyngocutaneous fistula is a common complication occurring in 17.5% of patients following total laryngectomy. Pharyngectomy and postoperative infection are independent risk factors for fistula formation.